Fracture Risk in Chronic Kidney Disease: Addressing an Overlooked Complication - Guido Gembillo; Concetto Sessa; Walter Morale; Luca Zanoli; Antonino Catalano; Salvatore Silipigni; Luca Soraci; Andrea Corsonello; Maria Princiotto; Carlo Lomonte; Domenico Santoro (Metabolites)
Fracture risk is a serious yet underrecognized complication among patients with chronic kidney disease (CKD), especially in those with stages G3-G5D. The overlap between CKD-Mineral and Bone Disorder (CKD-MBD) and osteoporosis leads to complex bone changes that increase the likelihood of fragility fractures. Studies show that 18% to 32% of CKD patients also have osteoporosis, and these individuals are more than 2.5 times as likely to suffer from fractures compared to those without CKD. In the advanced stages of the disease, fracture risk is up to four times higher than in the general population, with the femur, forearm, and humerus being the most commonly affected sites. Hip fractures are of particular concern as they are linked to longer hospital stays and higher rates of morbidity and mortality. Furthermore, dialysis patients who experience hip fractures have a mortality rate 2.4 times higher than those in the general population with similar fractures. This increased risk underscores the need for proactive bone health maintenance in CKD patients to prevent fractures and related complications. This review explores the underlying pathophysiological mechanisms, diagnostic challenges, and treatment options related to bone fragility in CKD. Diagnostic tools, such as bone mineral density (BMD) assessments, the trabecular bone score (TBS), and biochemical markers, remain underused, especially in advanced CKD stages. Recent treatment strategies emphasize a multidisciplinary, stage-specific approach, incorporating calcium and vitamin D supplements, anti-resorptive agents like denosumab, and anabolic therapies such as teriparatide and romosozumab. Effective management needs to be tailored to the patient’s bone turnover status and stage of CKD. Despite progress in understanding bone fragility in CKD, significant gaps remain in both diagnosis and treatment. Personalized care, guided by updated KDIGO recommendations and based on an interdisciplinary approach, is essential to reduce fracture risk and improve outcomes in this vulnerable population. Further research is needed to validate risk assessment tools and refine therapeutic protocols.